Doubled haploid rice lines production through anther culture of f1 derived from abiotic stress tolerant parents - Gunarsih, Cucu; Purwoko, Bambang Sapta; Dewi, Iswari Saraswati; Suwarno, Willy Bayuardi; Nafisah, (Universiti Kebangsaan Malaysia, 2022)
Anther culture is one of the feasible technologies for accelerating rice breeding programs. This research aimed at determining the anther culture ability and doubled-haploid plants production of eight F1s derived from single crosses between indica rice parents that had a single or multiple abiotic stresses tolerance. The experiment was conducted using completely randomized design (CRD) with 15 replications. Medium for callus induction was based on N6 + 2.0 mg L-1 NAA +0.5 mg L-1 kinetin + 1 mM putrescine, while the regeneration medium was based on MS + 0.5 mg L-1 NAA + 2.0 mg L- kinetin 1 + 1 mM putrescine. Medium for rooting was MS + 0.5 mg L-1 IBA. The results indicated that all F1 populations gave varied responses to callus induction and plant regeneration. The F1 populations from HS4-11-1-2/B13926E-KA-23 had higher anther culture ability compared to other seven F1 populations as indicated by the efficiency in callus formation and plant regeneration. Overall, the number of doubled haploid individuals (DHs) obtained was 158. F1 populations using HS4-11-1-2 as female parent, HS4-11-1-2/B13926E-KA-23 and HS4-11-1-2/CG8-93-1-1 contributed 45.4% and 34.9% doubled haploid individuals, respectively. The developed DHs lines need to be morphologically and agronomically characterized as well as screened under different combinations of abiotic stress to identify high-yielding and abiotic stress tolerant individuals for further rice breeding program.